Web Visual Design Principal Used in Public Universities in Malaysia - Bullah Affandy, Habee; Hussain, Azham; Mohd Nadzir, Maslinda (International Journal of Engineering and Technology, 2018)
Websites have become a vital tool for public universities. Universities websites are now becoming a hub for various services for various characteristics of users. With the increasing importance of a website, it resulted in new challenges for web designers. One of the challenges is ensuring that the web design incorporates both usability and pleasing web visual aesthetics. This research will look at the web visual design principles used by web designers in Malaysian public universities and the challenges faced by the web designers in designing the websites. Public universities web designers were interviewed for this research. The main findings of the research include the web design process of Malaysian public universities official websites, the web visual design principle used and the challenges faced by the web designers. This research also identified an opportunity for future research especially regarding the challenges faced by the web designers.Â Â